تقدير تحمّل أوراق بعض أصناف الحمضيات لدرجات الحرارة العالية - الراعي, جنان (Latakia University Journal -Biological Sciences Series, 2016)
The experiment was done within -2014 in plant physiology lab.of agriculture faculty of Tishreen University for estimation of high temperature stress toleration of citrus leaves in three varietis(Citrus Unshiu , Meyer Lemon,Citrus SinensisWashington). Many random samples of leaves were gathered from the foliage of the examined categories whereas tha average of the taken leaves was 200 from the whole sides for each one tree from the branches which are one year old . which were put for limited duration in a water bath about many different degrees of temperature then they were put in water and then in a solution of HCL acid .Many references were studied of containing :non spotting on leaves ,which means they are un harmed,simple spotting,the spotting of more than half of the leaves area,the perfect leaves spotting.Studied temperature were as the following :40-50-60-70-80.Each one of this mentiond temperature,40 leaves were used .The statistics analys were done with the way of Genstat 12,for the comparison between averages for the sake of calculating the least significant difference at the guidance level :5% .Studies showed that Satsuma leaves are the most toleration for high temperature,next Citrus SinensisWashington is less than Satsuma.At last Meyer Lemon was the least . نفذت التجربة خلال عام 2014-- في مخبر فسيولوجيا النبات التابع لكلية الزراعة بجامعة تشرين، بهدف تقدير تحمّل أوراق ثلاثة أصناف من الحمضيات لدرجات الحرارة المرتفعة (البرتقال أبو صرة واشنطن من مجموعة البرتقال، وصنف اليوسفي ساتسوما من مجموعة اليوسفي ، والصنف ماير من المجموعة الحمضية)؛ إذْ تم جمع عينات ورقية عشوائية من المسطح الورقي للأصناف المختبرة بمعدل 200 ورقة من كل صنف من جهات مختلفة للشجرة، ومن فروع بعمر سنة، ثم تمّ وضعها في حمّام مائي على درجات حرارة مختلفة مدة محددة، ثم وضعت في الماء العادي، وبعد ذلك غمست في محلول ضعيف من حمض كلور الماء 0.2 N .- درست بعد ذلك جملة من المؤشرات شملت عدم تبقع الورقة، ووجود تبقع بسيط ، وتبقع أكثر من نصف مساحة الورقة، وتبقع كامل الورقة. أما درجات الحرارة المدروسة فكانت على التوالي (40-50-60-70-80 ) ، وعند كل درجة حرارة على حده استخدمت 40 ورقة .أجري التحليل الإحصائي لمقارنة الفروق بين المتوسطات بحساب قيمة أقل فرق معنوي عند مستوى دلالة 5%. تبين نتيجة الدراسة أن أوراق اليوسفي ساتسوما أكثر تحملاً لدرجات الحرارة المرتفعة، تلاها البرتقال أبو صرة، بينما كان الصنف ماير أقلها تحملاً .